Obstacles to socioeconomic integration of low-skilled immigrants: A Spatial Approach in the Case of Greece - Bitsakos, Nikolaos (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2023)
The obstacles to socio-economic integration faced by low-skilled students with immigrant and refugee backgrounds attending Second Chance Schools and Second Chance Schools within detention facilities in Greece are examined. Specifically, the study investigates the extent to which these foreign learners experience social exclusion. The sample consists of students with immigrant and refugee backgrounds attending adult education facilities in the host country, including Second Chance Schools and Second Chance Schools within detention centers. The study approaches social exclusion in terms of economic, social, individual, and educational components, in order to identify the lack of resources, goods, rights, and services. A total of 320 students participated in the survey, with 165 attending Second Chance Schools and 155 attending Second Chance Schools within detention centers. The results highlight the significant socio-economic obstacles that drive social exclusion and are caused by low skills, including difficulty finding a job, job insecurity, and exploitation at work, particularly among students who have not completed compulsory education.